Answer :

Given, x4 + ax3 – 7x2 - 8x + b = 0

x = -2, -3 are a root of the above equation ( they are exactly divisible)


Substituting the value -2 and -3 in place of x will give,


(-2)4 + a (-2)3 7(-2)2 - 8(-2) + b = 0


16 8a 28 + 16 + b = 0


8a – b = 4 …. (i)


(-3)4 + a (-3)3 7(-3)2 - 8(-3) + b = 0


81 27a 63 + 24 + b = 0


27a – b = 42 …. (ii)


Simultaneously solving eq(i) and eq(ii) we get,


a = 2


b = 12


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Structural Organisation In Animals-IStructural Organisation In Animals-IStructural Organisation In Animals-I54 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

The zeroes of theRS Aggarwal & V Aggarwal - Mathematics

Zero of the polynRS Aggarwal & V Aggarwal - Mathematics

If 2 and -1/3 areRS Aggarwal & V Aggarwal - Mathematics

If (x + 1) is a fRS Aggarwal & V Aggarwal - Mathematics

If (x2RS Aggarwal & V Aggarwal - Mathematics

The zeroes of theRS Aggarwal & V Aggarwal - Mathematics

The zeroes of theRS Aggarwal & V Aggarwal - Mathematics

If p(x) = x3RS Aggarwal & V Aggarwal - Mathematics

If p(x) = (xRS Aggarwal & V Aggarwal - Mathematics

The coefficient oRS Aggarwal & V Aggarwal - Mathematics